An Integrated Analysis for Post Hydraulic Fracturing Production Forecast in Conventional Oil Sand Reservoir - Dedy Kristanto; IMD Saputra Jagadita (Journal of Earth Energy Engineering, 2021)
Hydraulic fracturing is one of the stimulation treatment in oil and gas well by creating a fractured through a proppant injection to the formation. A most critical problem in the actual oil and gas industry is that the fracturing engineers could not forecast approximately post-production performance after fracturing the job, which is a severe problem. This problem phenomenon has occurred in some cases and significantly impacts production such as oversizing or lower sizing of pumping rate setting. Integrated analysis for post job hydraulic fracturing production based on the geometry model iteration and Productivity Index (PI) comparison in the conventional oil sand reservoir is simply a method to analyze and forecast approximately incremental production performance. The fractured software generates a fractured geometry model that considers half-length of fractured parameters, width in front of perforation, average width, fractured height, and pressure net. Then we compare the Productivity Index's prediction value through the method of Cinco-Ley, Samaniego and Dominguez. A case study in the well of TM#2 (conventional oil sand reservoir) was conducted as the comprehensive study to provide the data and proceed analysis for production forecast. We found that the geometry model and iteration of PKN 2D method generated a small fractured geometry model compare to fracCADE software. The cooperation between PKN 2D method and Cinco-Ley, Samaniego, and Dominguez concept successfully predict post-production forecast. This concept could be proposed as a quick look measurement for production scenarios to overcome pump sizing.